STRATEGI PEMERINTAH DAERAH DALAM MENGEMBANGKAN OBJEK WISATA DI KABUPATEN BOLAANG MONGONDOW UTARA - .., Bustamin; Sambiran, Sarah; Rondonuwu, Arpi (JURNAL EKSEKUTIF, 2017)
AbstractEach region in Indonesia has a unique in terms of beauty and customs that exist in the area so as to attract tourists to visit it. To enhance the role of tourism, it is closely related among the goods in the form of own attractions that can be sold by means and infrastructure that support it related in the tourism industry. Enterprises to develop a tourist destination should pay attention to various factors that affect the existence of a tourist destination. North Sulawesi Province which used to have the nickname "Torang Samua Basudara" and now changed to "Torang Samua Ciptaan Tuhan". has four Municipalities and eleven Regencies, one of them is Kabupaten Bolaang Mongondow Utara. Currently, the management of tourist attraction in Bolaang Mongondow Utara Regency has not been well managed, such as management management is still not professional, lack of tourism activity, facilities and infrastructure is still inadequate, the process of providing information has not been organized or delivered properly. By looking at the situation is required a management role for the delivery of good information will be a tourist attraction in the District of North Bolaang Mongondow to the outside community to know and can enjoy the facilities provided in the attraction.Keywords : Strategy, Local Government, North Bolaang Mongondow, Tourism Object